Clinical Efficacy of Two Novel, Differentially Administered (IM, ID) Vaccines against Mycoplasma hyopneumoniae and PCV2 in Swine under Field Conditions - Wolfgang Sipos; Sabine Sipos (Animals, 2022)
Enzootic pneumonia (EP) of pigs is caused by Mycoplasma hyopneumoniae (M.hp.), which is, together with the porcine circovirus type 2 (PCV2), among the most prominent inducers of the porcine respiratory disease complex (PRDC). Therefore, vaccination of piglets against M.hp. and PCV2 is crucial in the fight against pulmonary infections. In this field study, we tested the clinical efficacy of two novel vaccines, one delivered IM (Hyogen® + Circovac®) and the other ID (MHyo-Sphere®PCV ID), on a fattening farm in Lower Austria with a history of still ongoing EP. Average daily weight gain, coughing/sneezing index, losses due to morbidity/mortality, and lung scoring data at slaughter by means of CLP (Ceva Lung Program) were recorded for three consecutive fattening cohorts to achieve a powerful number of animals, one half each vaccinated with the IM vaccine and the other half with the ID vaccine (n = 659 in total). No statistically significant differences could be observed between the two vaccination groups for the parameters investigated, but the total median EP score, which categorizes pulmonary lesions due to infection by M.hp. with a theoretical range of 0–28, was lowered from initially 1.9 to 1.0, indicating that both vaccines proved very suitable measures in the fight against EP.